Metacognition in Argumentative Writing Based on Multiple Sources in Geography Education - Gebele, Diana; Zepter, Alexandra L.; Königs, Pia; Budke, Alexandra (European Journal of Investigation in Health, Psychology and Education (EJIHPE), 2022)
This paper addresses questions about the use of metacognitive strategies in argumentative writing based on multiple sources and the influence of this use on the quality of student texts. For this purpose, think-aloud protocols and texts from a research project on material-supported argumentative writing in 8th grade geography lessons are analyzed and discussed. The analysis is based on a model of metacognition in argumentative writing using multiple sources, which we also propose in this paper. The results show that the use of metacognitive strategies is a challenge for the investigated target group but that their use, in particular the deployment of goal-setting strategies and planning strategies, enables students to write better texts.